Simplex Lattice Strength Optimization of Lime-micro Silica Stabilized Coir Fiber-reinforced Soil - Emmanuel, E. (Taylor and Francis Inc., 2020)
The current study aimed at using a simplex lattice mixture design in designing the experiments, evaluating the results, and optimizing the contents of lime, micro silica, and coir fiber for enhancing the strength property of a residual soil. The effect of the independent variables (lime content, micro silica content, and coir fiber content) on the strength property (unconfined compressive strength (UCS)) was investigated by analysis of variance. Besides, strength optimization was carried out using the desirability function approach to determine the optimum additive combinations in achieving maximum strength. The results showed that the fitted model demonstrated a high determination coefficient (98.61). The optimization of the variables illustrated that utilizing 7.10 micro silica, 2.32 lime, and 0.59 coir fiber produced an optimum UCS of 827.93 kPa with a designated maximum desirability function of (DÂ =Â 1.00). Also, the predicted optimum combinations were experimentally tested to check the accuracy and dependability of the optimized conditions. The findings show a good correlation between the experimental values and the predicted optimized values by the developed model. Therefore, the developed model is rationally accurate for forecasting the UCS of the lime-micro silica stabilized coir fiber-reinforced soil. Â© 2020 Taylor & Francis.